2019
DOI: 10.1016/j.lindif.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionality in the measurement of math-specific anxiety and its relationship with mathematical performance

Abstract: Traditionally, mathematical anxiety has been utilized as a unidimensional construct. However, math-specific anxiety may have distinguishable factors, and taking these factors into account may better illuminate the relationship between anxiety and mathematics performance. Drawing from the Western Reserve Reading and Math Project (N = 244 children, mean age = 12.28 years), the present study examined math-specific anxiety and mathematics problem evaluation, utilizing a structural equation modeling approach with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
0
40
0
1
Order By: Relevance
“…Additionally, math anxiety is predictive of math test performance even when test anxiety is controlled for (cf. Lukowski et al, 2016). Similarly, when students simply anticipate doing math, those high in math anxiety show greater activity in brain regions associated with visceral threat detection and the experience of pain (dorsoposterior insula) than those low in math anxiety (Lyons & Beilock, 2012).…”
Section: The Bidirectional Relation Between Math Anxiety and Math Permentioning
confidence: 99%
“…Additionally, math anxiety is predictive of math test performance even when test anxiety is controlled for (cf. Lukowski et al, 2016). Similarly, when students simply anticipate doing math, those high in math anxiety show greater activity in brain regions associated with visceral threat detection and the experience of pain (dorsoposterior insula) than those low in math anxiety (Lyons & Beilock, 2012).…”
Section: The Bidirectional Relation Between Math Anxiety and Math Permentioning
confidence: 99%
“…There have been nearly 20,200 previous studies related to MA or math performance (Olmez and Ozel, 2012; Necka et al, 2015; Lukowski et al, 2016; Justicia-Galiano et al, 2017), while few systematic studies focus on exploring the math anxiety-performance link during the previous 19 years. Two previous meta-analyses that were conducted 30 or 40 years ago concluded that there was a small but robust negative math anxiety-performance link in students (Hembree, 1990; Ma, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the instruments used to measure MA, different factor structures were found. The four most common factors are anxiety about math tests [1113], anxiety about performing numerical operations [1112, 14], anxiety about performing math in social situations [1213], and anxiety about observing and learning materials in math [3, 15]. With respect to motivation, the three most studied dimensions are self-perceived ability, interest, and importance [2].…”
Section: Introductionmentioning
confidence: 99%